Gender-responsive nature-positive solutions for resilient agri-food systems - Kinuthia, Dickson; Wallin, Elsa; Bryan, Elizabeth; Davis, Kristin E.; Oingo, Balentine (International Food Policy Research Institute, 2023)
Nature-positive solutions (NPS) seek to address the negative effects of climate change, restore biodiversity, and sustainably manage land and water resources through strategies implemented at farm and community levels, drawing on both traditional and scientific knowledge, while ensuring that agriculture stays within planetary boundaries. Given gender differences in livelihood roles, control over resources, and influence over livelihood decisions, men and women have different needs from and preferences for nature-positive solutions. Moreover, production choices within agri-food systems have differential implications for men and women, including their labor burden and exposure to health hazards from unsustainable farming practices. The CGIAR Initiative on Nature-Positive Solutions is conducting a study in Colombia, India, Kenya and Vietnam using mixed methods to understand the gender-differentiated perceptions of NPS and the incentives for and barriers to their implementation. Preliminary results from Kenya indicate that women play critical roles in forest restoration and soil fertility improvement, among other practices. However, women continue to face constraints to accessing productive resources and services—such as land, finance and extension services—and have more limited decision-making authority over production and spending decisions despite their significant contributions. Accelerating the uptake of NPS requires addressing these gendered constraints to adopting these practices. This study suggests this can be accomplished by promoting solutions such as NPS gendered-training, and ensuring that women have the resources and services to support their uptake, leading to more resilient and sustainable agri-food systems.